(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
With rising product consumption all around the country, the Indian economy is expandingquickly. Due to Make in India and rising consumer demands, it is becoming more difficult to safeguardthe environment while also meeting customer desires. Numerous experts have seen over the past fewdecades a significant shift in consumer behavior from selecting products based on factors like size, color,and flavour to other more significant ones like environment and health. Businesses have seen this shift inconsumer behavior. As part of their corporate social responsibility efforts, they are implementingenvironmentally friendly methods into the designing, manufacturing, packaging, and marketing of theirgoods and services in an effort to gain an advantage in the competitive market. The main goal of thestudy is to determine how different natural cosmetics consumers’ consumption habits are and toillustrate the enormous influence that green marketing has on the cosmetics business as a fresh,promising future development for everyone.The study identifies the variables that affect consumer decisions to purchase green products. Thefindings are unique in that customers grouped according to preference for green cosmetics. Theinformation gathered in Chandigarh, India between the months of November and December 2022 utilizingan online questionnaire. 210 people responded to our questions.Suitable statistical methods were usedto test the information gathered from the respondents. Results revealed that some consumers likednatural cosmetics while others opted to purchase chemical ones. The findings indicate that health andenvironmental awareness will be a prominent trend for both on the market for cosmetic items.There wasno clear correlation between male and female respondents’ allegiance to particular cosmetic brands.